Evaluation of Student-Centred Facilities in Southwestern Nigerian Public Universities Hostels - Oyebamiji Israel Motolani; Oyadokun Joel Olufemi; Olutoye Toluwanimi Caleb (International Journal of Advanced Academic Research, 2026)
University hostel accommodation in Nigeria serves far more than a sleeping space, it is foundational for academic success, social interaction, and student well-being. However, many public universities in Southwestern Nigeria continue to experience persistent and systemic deficiencies in hostel provision. These challenges include inadequate accommodation capacity, poor maintenance culture, overcrowding, insufficient student-centred facilities, unreliable utility services, and deteriorating physical conditions, all of which negatively affect students’ comfort, health, academic performance, and quality of campus life. This study therefore evaluates the student-centred facilities in southwestern Nigerian public universities hostels with a view to making appropriate suggestions that will improve student’s performance and control overcrowding. A quantitative survey design was adopted, and data were collected through structured questionnaires administered to students across six universities namely, University of Lagos, Olabisi Onabanjo University, University of Ibadan, Obafemi Awolowo University, Federal University of Technology Akure, and Ekiti State University. 350 questionnaires were distributed, 333 were retrieved and found valid for analysis, representing a 95.1% response rate. Descriptive statistics, mean weighted values, cross-tabulation, correlation analysis, and prioritization ranking were used to analyze the data. The findings showed that core utilities such as electricity, water supply, and security were relatively stronger than support facilities such as ICT infrastructure, study rooms, kitchen areas, laundry spaces, and recreational spaces. It also revealed weaknesses in maintenance culture, overcrowding, noise control, toilet facilities, and bathroom provision. Students placed the highest priority on water supply, electricity, ICT facilities, study spaces, and sanitation. The study concluded that student-centred hostel facilities in Southwestern Nigerian public universities were unevenly provided and require stronger management attention to support student welfare and academic life. It recommends that hostel development should integrate ICT support, study areas, kitchens, recreation, accessibility, and preventive maintenance from the outset.